Collaborative construction using chat in different tasks - Roselli, Néstor (2011)
The objective of this research was to characterize the chat collaborative interaction of two partners in six kinds of cognitive tasks. The central hypothesis was that the task nature determines a particular kind of collaborative interaction. The six tasks tested were: to solve a logical problem, to compose a story, to read a data table, to rank opinions, to bring a scientific explanation of a domestic situation, to interpret the signification of a literature text. The 11 dyads of the sample were formed by university students. Results show significant differences between the tasks concerning the sociocognitive interaction, specially the logical-intelligent tasks related the open-interpretative tasks. Finally, there is a great difference between tasks in the personal evaluation of the difficulty and interest of each one.